Dukungan Manajerial sebagai Faktor Pendorong Kreativitas Karyawan: Studi Kasus di PT Byrnecut Indonesia - Purba, Yessica Pauline Riani; Ismail, Iriani (Lembaga Yasin AlSys, 2025)
This study aims to identify the effect of managerial support on employee creativity levels. The background of this research is the need for companies in the mining industry to continually innovate and face operational challenges. This research employed a qualitative approach with a case study method, where data was collected through in-depth interviews with employees and managers of PT Byrnecut Indonesia. The results show that managerial support, whether in the form of resources, guidance, or feedback, plays an important role in facilitating employee creativity. Employees who receive good managerial support tend to be more motivated to generate new ideas and contribute to company innovation. The conclusion of this study confirms the importance of management’s role in creating an environment conducive to creativity, which ultimately contributes to organizational success.